Brain Fluid Content Related to Body Position and Postmortem Interval – An Animal Model. Issue 3 (15th February 2016) - Leonard, Anna; Vink, Robert; Byard, Roger W.
Abstract: Adult male Sprague Dawley rats were euthanized and placed in a horizontal or vertical (head‐down) position at room temperature, after which brain fluid content was measured by a moisture analysis technique at variable time points. No significant difference in brain fluid content was observed between horizontal and vertical postmortem positions. A significant increase in brain fluid content was demonstrated 3, 6, and 24 h after death, with maximal fluid content observed at 24 h. Specifically, the brain fluid content of control animals was 77.79 ± 0.36%, increasing to 80.05 ± 0.22% at 24 h ( p < 0.0001). This study has demonstrated no significant differences in brain fluid content related to postmortem position, suggesting that a head‐down position is not associated with increased brain fluid content or swelling. However, significant temporal increases in brain fluid content after death, most likely related to cerebral liquefaction, occur.